Identification of drought tolerant inbred lines and assessment of combining ability in maize (Zea mays L.) - Shailaja, D.S.; Lohithaswa, Hirenallur Chandappa; Sowmya, M. S.; Mallana Gowdra Mallikarjuna; Banakara, Santhoshkumari; Likhithashree, T. R.; Kirankumar, R.; Basanagouda, G.; Patne, Nagesh; Vivek, Bindiganavile S. (Wiley, 2024)
Maize is an important agricultural crop ensuring food and nutritional security throughout the globe. It is highly sensitive to many of the biotic and abiotic stresses, and among them, drought is the most severe abiotic stress limiting maize production. Climate change tends to worsen this scenario by changing precipitation patterns and decreasing water availability. Hence, the present study was undertaken to identify drought-tolerant inbred lines under well-irrigated and managed stress conditions in the field toward developing drought-resilient maize hybrids. The initial in vitro screening of 65 agronomically elite maize inbred lines was undertaken at 15%, 20%, and 25% polyethylene glycol (PEG) concentrations. Subsequently, the 15 inbreds selected for their promising performance under varying concentrations of PEG were evaluated in the pot (100%, 60%, and 40% of field capacity [FC]) and managed field experiments (moisture stress). Various physiological, biochemical, and yield attributing traits were measured among the inbreds to assess their drought tolerance potential. The analysis of variance in the pot and field experiments indicated significant genotypic differences among the inbreds and genotype × treatment interaction for different traits considered. In the pot experiment, the phenotypic correlation analysis showed a significant positive association of shoot fresh weight with plant height (r = .71), number of leaves (r = .58), relative water content (r = .60), root fresh weight (r = .58), shoot dry weight (r = .60), and SPAD meter readings under (r = .71) moisture stress condition. In the field experiment, the grain yield had a significant positive association with plant height, relative water content, SPAD before stress, ear length, ear girth, kernel rows per ear, kernels per row, and per day productivity under stress. Proline accumulation in inbreds during stress was found to be higher compared to nonstress conditions. The inbred lines CML 505, CML 444, CML 451, CML 504, QM 11408, and MAI 214 were promising for most of the drought tolerance imparting traits. These six inbreds along with four inbreds having low DRI (SKV 50, MAI E2-163, MAI 16, and MAI E2-241) were crossed in half diallel manner, and crosses involving low × high or high × low DRI inbreds showed higher grain yield. The current study also revealed the need of combining various physiological and yield attributing traits in drought breeding programmes.